Dough rheological properties and texture of gluten-free pasta based on proso millet flour. (March 2017) - Motta Romero, Hollman; Santra, Dipak; Rose, Devin; Zhang, Yue
Abstract: Proso millet (PM) is a gluten-free cereal grain with potential to be used in gluten-free product development. However, research on improving the rheological properties of PM dough is limited. In the present study, rheological and color characteristics of PM dough (37% moisture) were compared with the behavior of wheat dough. Three hydrocolloids [guar gum (GG), xanthan gum (XG) and sodium alginate (SA)] at concentrations of 0%, 1% and 2% were added to improve the physical properties of PM dough. The textural properties of PM dough developed pasta with hydrocolloids were also studied. Wheat dough presented a much higher apparent viscosity and elastic modulus than PM dough. Both the apparent viscosity and elasticity were increased by all three hydrocolloids, with 2% XG presenting the most pronounced improvement in elasticity. Generally, the capacity of hydrocolloids to improve the PM dough follow the order XG > GG > SA. The addition of hydrocolloids showed no significant impact on the color of PM dough. GG and XG showed an improvement in the network strength of PM pasta, while SA did not contribute to textural enhancement. Highlights: Proso millet (PM) was utilized as the sole ingredient to produce gluten-free pasta. The rheology of PM dough was improved by sodium alginate (SA), guar gum (GG) and xanthan gum (XG). XG and GG improved the texture of PM pasta while SA had no contribution. Hydrocolloids did not significantly affect the color of proso millet dough.